Exact and kernelization algorithms for Closet String (Selecciones Matemáticas, 2020)
In this paper we address CLOSEST STRING problem that arises in web searching, coding theory and computational molecular biology. To solve it is to find a string that minimizes the maximum Hamming distance from a given set of strings. CLOSEST STRING is an NP-hard problem. This paper proposes two linear-time algorithms, one for the general case, a kernelization algorithm, and the other for three-strings, a linear-time algorithm called Minimization First Algorithm (MFA). A formal proof of the correctness and the computational complexity of the proposed algorithms are given.